(untitled) (Global Journal of Human-Social Science, 2020)
Metaphoric space of discourse is understood as a part of the semantic space of discourse formed on the complex relationships between the semantic spaces of the source-area and the target-area as well as within these areas in the whole set of discourse metaphors. The structure, algorithm and approaches to modeling the metaphorical space of discourse and its model are demonstrated on the example of vocal-pedagogical discourse.